2019
DOI: 10.1029/2019ja026651
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Cosmic Rays' Atmospheric Effects and Their Relationships to Cutoff Rigidity and Zenith Angle Using Global Muon Detector Network Data

Abstract: Cosmic rays are charged particles whose flux observed at Earth shows temporal variations related to space weather phenomena and may be an important tool to study them. The cosmic ray intensity recorded with ground-based detectors also shows temporal variations arising from atmospheric variations. In the case of muon detectors, the main atmospheric effects are related to pressure and temperature changes. In this work, we analyze both effects using data recorded by the Global Muon Detector Network, consisting of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 57 publications
(88 reference statements)
0
7
0
Order By: Relevance
“…variations due to the temperature effect are approximated by |ΔRR0T=αMSS0.25emΔTMSS TMSS=truei=1nTi·()xfalse(hifalse)xfalse(hi+1false)xfalse(h0false) where x ( h i ) is the atmospheric depth at the same altitude. Indeed, a very recent study from the GMDN (Mendonça et al., 2019) found a relation between the mass‐weighted temperature coefficient and the cutoff rigidity ( R c ) and latitude ( L ) for vertical incidence: αMSS=0.304+0.0389·normallnRc0.0488·normalsinL …”
Section: Resultsmentioning
confidence: 99%
“…variations due to the temperature effect are approximated by |ΔRR0T=αMSS0.25emΔTMSS TMSS=truei=1nTi·()xfalse(hifalse)xfalse(hi+1false)xfalse(h0false) where x ( h i ) is the atmospheric depth at the same altitude. Indeed, a very recent study from the GMDN (Mendonça et al., 2019) found a relation between the mass‐weighted temperature coefficient and the cutoff rigidity ( R c ) and latitude ( L ) for vertical incidence: αMSS=0.304+0.0389·normallnRc0.0488·normalsinL …”
Section: Resultsmentioning
confidence: 99%
“…Here the temperature coefficient α T and the effective temperature T ef f are defined as Theoretical (Dmitrieva et al, 2011) This work ∆α α T (%/K) -0.319 -0.279 ± 0.051 0.040 ± 0.051 (Mendonça et al, 2019) This work ∆α α M SS (%/K) -0.271 -0.233 ± 0.045 0.038 ± 0.045…”
Section: Resultsmentioning
confidence: 99%
“…where x(h i ) is the atmospheric depth at the same altitude. Indeed, a very recent study from the GMDN (Mendonça et al, 2019) found a relation between the mass-weighted temperature coefficient and the cutoff rigidity (R c ) and latitude (L) for vertical incidence:…”
Section: Resultsmentioning
confidence: 99%
“…There are 6 Â 6 in the first, 4 Â 4 in the second and 4 Â 9 individual detectors in the third. On the other hand, the Kuwait telescope is composed of four 5 Â 5 m layers (0.8 m apart) of cylindrical proportional counter tubes below a lead layer (Mendonça et al, 2019). When a coincidence is registered between two detectors, one at each layer, the trajectory of a particle can be determined.…”
Section: Introductionmentioning
confidence: 99%